2020
DOI: 10.1109/access.2019.2961609
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Non-Linear Covert Channel Detection in TCP Data Streams

Abstract: Cyber-attacks are causing losses amounted to billions of dollars every year due to data breaches and vulnerabilities. The existing tools for data leakage prevention and detection are often bypassed by using various different types of sophisticated techniques such as network steganography for stealing the data. This is due to several weaknesses which can be exploited by a threat actor in existing detection systems. The weaknesses are high time and memory training complexities as well as large training datasets.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…ML for covert channel detection has been widely studied [54]. Nafea et al indicated that the SVM algorithm is the best approach for detecting covert data [55]. However, the success of ML approaches depends on the availability of the traffic samples that represent many types of covert channels, and not only traffic samples that represent specific types of covert channels.…”
Section: Covert Channels Detectionmentioning
confidence: 99%
“…ML for covert channel detection has been widely studied [54]. Nafea et al indicated that the SVM algorithm is the best approach for detecting covert data [55]. However, the success of ML approaches depends on the availability of the traffic samples that represent many types of covert channels, and not only traffic samples that represent specific types of covert channels.…”
Section: Covert Channels Detectionmentioning
confidence: 99%
“…The centralized database stores all the data for further processing and analyzing. The data is collected from the construction activities that start from planning and completion phases [31,32]. As security is one of the challenge especially when the data transmitted to the edge computing or to the cloud for further decision making, we proposed a IDS solution at the edge computing side to protect all the data coming from ground network and sensor devices.…”
Section: Security Model For the Sustainable Development-related Data Securitymentioning
confidence: 99%
“…In the steganography process, SIP tags are used as the carrier of secret information, so the detection end first calculates the three-dimensional vector of each tag, and later obtains the distance vector between the vectors in the reconstruction space. Then, a comparison is made to determine whether it contains steganographic information after calculating the third-order feature value and the threshold [99]. The experimental results showed that the computational complexity was low, and was appropriate for online operation.…”
Section: Steganalysis Based On the Application Layermentioning
confidence: 99%